Pomiar zależności między ekstremalnymi stratami na polskim rynku akcji i na wybranych rynkach światowych - Rokita, Paweł (Extreme Value Dependence Estimation for Stock-Investment Losses in Poland and Some Other Markets, 2007)
This paper reports on some research in extreme-value dependence for returns of WIG20 index (the index comprising stocks of the 20 biggest companies in Warsaw Stock Exchange) and relative indices of some other markets. Asymptotic dependence concept is utilized and tail dependence coefficient (TDC) - a measure of asymptotic dependence - is estimated. The article is a continuation of a former research, whose aim was testing for existence of asymptotic dependence between stock market indexes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 131-140